An ecumenical framework in Mbiti’s African theology - Mbaya, Henry (Stellenbosch Theological Journal, 2024)
This study discusses the theological framework of John Mbiti’s African theology. It has identified Konrad Raiser’s “Ecumenical paradigm” as a framework within which to conceptualize and understand Mbiti’s theological works, approach, and perspectives. The study argues that Mbiti works with an ecumenical paradigm and framework of African religion(s) and culture. Raiser’s metaphor of “One Household of Life”, is an important theological conceptual tool to try to grasp Mbiti’s approach and methodology. Taking an ecumenical approach, Raiser argues the importance of religions and faith confessions of engaging in dialogue and communication. Behind dialogue, lies the more critical question of the authority of the local context and religions, in relations to Western Christianity. Mbiti wrestles with the question: what authority does African Tradition Religion (ATR) have in relation to Western Christianity, and other religions? Further the study, highlights that there are two principles that are at work in Mbiti’s theological framework and approach, namely, the local in relation to the universal, and the normative in relation to the relative, which can also be understood as the absolutizing in relation to the relativizing.